Improving Students' Writing Descriptive Text Through Digital Storytelling Technique - Karisma Erikson Tarigan; Liana Liana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The most difficult part of writing is students could not organize the development of their ideas and the purpose of the text.Digital storytelling is one of the multimedia to improve students' writing competency. The main objective of this research is to prove whether the digital storytelling enhances and improve students writing competency. The study uses classroom action research (CAR). The data in this study are quantitative and qualitative data. The quantitative data will be collected by using the essay test. The qualitative data will be collected by using observation, field notes, and questionnaire.The results of the use of digital storytelling in writing text significantly increased by using digital storytelling. The score of students’ writing descriptive text kept increasing from pre-test until post-test. It was proved by the data which showed that the mean of the students’ score in post-test II (86.4) was higher than the post-test I (72.2), and also higher than the pre-test (54.8). in addition, the response of student in using digital storytelling in the agree category, it can be seen from the frequencies of item 110 (52.88%).Therefore, Digital Storytelling significantly improves students’ score in writing Descriptive Text. Furthermore, it can be concluded that Digital Storytelling is effective to be used in teaching writing skill, especially in Descriptive Text.